2020
DOI: 10.1142/s0129065720500124
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble Deep Learning on Large, Mixed-Site fMRI Datasets in Autism and Other Tasks

Abstract: Deep learning models for MRI classification face two recurring problems: they are typically limited by low sample size, and are abstracted by their own complexity (the "black box problem"). In this paper, we train a convolutional neural network (CNN) with the largest multi-source, functional MRI (fMRI) connectomic dataset ever compiled, consisting of 43,858 datapoints. We apply this model to a crosssectional comparison of autism (ASD) vs typically developing (TD) controls that has proved difficult to character… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 81 publications
0
66
0
1
Order By: Relevance
“…For example, Lu et al [ 65 ] proposed a multi-kernel-based subspace clustering algorithm for identifying ASD patients, which still has a good clustering effect on high-dimensional network datasets. Leming et al [ 66 ] trained a convolutional neural network and applied it to ASD recognition, and their experiments showed that deep learning models that distinguish ASD from NC controls focus broadly on temporal and cerebellar connections. However, the problem of small size fMRI data prevented the generalization of the above research works [ 67 ].…”
Section: Related Workmentioning
confidence: 99%
“…For example, Lu et al [ 65 ] proposed a multi-kernel-based subspace clustering algorithm for identifying ASD patients, which still has a good clustering effect on high-dimensional network datasets. Leming et al [ 66 ] trained a convolutional neural network and applied it to ASD recognition, and their experiments showed that deep learning models that distinguish ASD from NC controls focus broadly on temporal and cerebellar connections. However, the problem of small size fMRI data prevented the generalization of the above research works [ 67 ].…”
Section: Related Workmentioning
confidence: 99%
“…A number of studies have leveraged the power of ML methods to build flexible nonlinear mapping models and use them to identify neural correlates of brain disorders (e.g., Hasanzadeh et al, 2019;Kazemi & Houghten, 2018;Kim et al, 2016;Leming et al, 2020) and behavioral traits (e.g., Kumar et al, 2019;Morioka et al, 2020;Xiao et al, 2019). Yet the vast majority of cognitive neuroscience studies use linear mapping models (such as linear regression), resulting in a gap between different neuroscience subfields.…”
Section: The Controversymentioning
confidence: 99%
“…These 12 feature set variants were applied to both the raw and de-seasonalized training data. [89][90][91][92]. For all ML tools except for MLR, parameters were optimized via grid search with three fold validation, using the time series cross-validator implemented in scikit-learn [93].…”
Section: Feature Selectionmentioning
confidence: 99%